Ảnh hưởng của ông bà tới việc chăm sóc và giáo dục cháu - Lại, Vũ Kiều Trang (Tạp chí thiết bị giáo dục, 2023)
With the continuous development of the economy Society, adults often work with jobs to meet the increasing financial requirements of the family. Although giving birth and educating children is a parent's right and obligation, in some families, especially those with multiple generations, he is often the one to take care of and educate the grandchildren, when parents go to work. This thing offers significant benefits but also many negative effects. The article summarizes the research on his influence on the design work and the education of children. It is the basis for in-depth studies in the field of family studies and sociology. Keywords: Grandparents, care, grandchildren, family